EFFECTS OF INDEX OPTION CONTRACTS AND FUSION OF EXCHANGES ON DERIVATIVE MARKETS: AN EMPIRICAL ANALYSIS ON BORSA ISTANBUL (Third Sector Social Economic Review, 2020)
In this study, the appropriate volatility model is investigated for index futures contracts that are heavily traded in Borsa Istanbul. The analysis covers the dates from January 04, 2010 to December 31, 2018. Symmetrical and asymmetrical volatility models, ARCH, GARCH, T-GARCH, E-GARCH and PARCH, were tested in the selection of the appropriate structure. Then, the effects of index option contracts, which began trading at a later date, and fusion of exchanges cases on index futures contracts were examined. Index option contracts are considered as financial innovation in terms of alternative investment element, and fusion of exchanges are considered as technical innovation in terms of providing synchronization in transactions. It is determined that index option contracts are positively and fusion of exchanges negatively effects index futures contracts’ volatility.
Keywords: Derivatives Markets; Borsa Istanbul; Index Futures Contracts; Index Options Contracts; Fusion of Exchanges; GARCH Models